Character Education Strengthening of Students Through The Mathematical Disposition Strategy on Statistics Elementary - Ahmad Yani; Kurnia Ningsih (JPMI (Jurnal Pendidikan Matematika Indonesia), 2019)
This study aims to improve the strengthening of student character education through a mathematical disposition strategy in Elementary Statistics. The sample of this study was 30 students of the 3rd semester of Biology Education. The research method used was experimental and the research firm was quasi-experimental. Data collection techniques are measurement techniques, namely initial ability tests and mathematical disposition scales. The results of this study indicate that character education can be enhanced or strengthened by a mathematical disposition strategy. That is by increasing high confidence in solving problems, not easily discouraged and asking questions, having prepared before starting learning such as reading the material or other references, knowing the role of mathematics related with everyday life and knowing that success in mathematics subjects can support progress in other disciplines.